"Poverty, Inequality and prises in rural India." (New Delhi, 1991)
The main objective of this study is to examine if changes in the relative price of food had any impact on rural poverty in India since the 1950 and, if so, to access the nature and extent of this effect. Since consumption of food in the urban sector is met by supplies from the rural sector and the relative price of food in the rural sector is affeceted by, among other things, the demand in the urban sectir, an investigation of this kind needs to be carried out in a framework which distinguishes beween these two sectors.
Keywords: Prices India